Construction of Biomimetic-Responsive Nanocarriers and their Applications in Tumor Targeting - Tian, Xuexia; Shi, Anhua; Wu, Junzi (Anti-Cancer Agents in Medicinal Chemistry, 2022)
Background: At present, tumors are leading cause of death. Biomimetic nanocarriers for precision cancer therapy are attracting increasing attention. Nanocarriers with a good biocompatible surface could reduce the recognition and elimination of nanoparticles as foreign substances by the immune system, offer specific targeting, and improve the efficacy of precision medicine for tumors, thereby providing outstanding prospects for application in cancer therapy. In particular, cell membrane biomimetic camouflaged nanocarriers have become a research hotspot because of their excellent biocompatibility, prolonged circulation in the blood, and tumor targeting. Objective: The objective of this study is to summarize the biological targeting mechanisms of different cell membraneencapsulated nanocarriers in cancer therapy. In this article, the characteristics, applications, and stages of progress of bionic encapsulated nanocarriers for different cell membranes are discussed, as are the field’s developmental prospects. Methods: The findings on the characteristics of bionic encapsulated nanocarriers for different cell membranes and tumor treatment have been analyzed and summarized. Results: Biomimetic nanosystems based on various natural cell and hybrid cell membranes have been shown to efficiently control targeted drug delivery systems. They can reduce immune system clearance, prolong blood circulation time, and improve drug loading and targeting, thereby enhancing the diagnosis and treatment of tumors and reducing the spread of CTCs. Conclusion: With advances in the development of biomimetic nanocarrier DDSs, novel ideas for tumor treatment and drug delivery have been emerged. However, there are still some problems in biomimetic nanosystems. Therefore, it needs to be optimized through further research, from the laboratory to the clinic to benefit a wide range of patients.
Keywords: cell membrane